Fibrin(ogen)olytic and antiplatelet activities of a subtilisin-like protease from Solanum tuberosum (StSBTc-3) - Pepe, Alfonso (2016)
Plant serine proteases have been widely used in food science and technology as well as in medicine. In this sense, several plant serine proteases have been proposed as potential anti-coagulants and anti-platelet agents. Previously, we have reported the purification and identification of a plant serine protease from Solanum tuberosum leaves. This potato enzyme, named as StSBTc-3, has a molecular weight of 72 kDa and it was characterized as a subtilisin like protease. In this work we determine and characterize the biochemical and medicinal properties of StSBTc-3. Results obtained show that, like the reported to other plant serine proteases, StSBTc-3 is able to degrade all chains of human fibrinogen and to produces fibrin clot lysis in a dose dependent manner. The enzyme efficiently hydrolyzes β subunit followed by partially hydrolyzed α and γ subunits of human fibrinogen. Assays performed to determine StSBTc-3 substrate specificity using oxidized insulin β-chain as substrate, show seven cleavage sites: Asn3-Gln4; Cys7-Gly8; Glu13-Ala14; Leu15-Tyr16; Tyr16-Leu17; Arg22-Gly23 and Phe25-Tyr26, all of them were previously reported for other serine proteases with fibrinogenolytic activity. The maximum StSBTc-3 fibrinogenolytic activity was determined at pH 8.0 and at 37 C. Additionally, we demonstrate that StSBTc-3 is able to inhibit platelet aggregation and is unable to exert cytotoxic activity on human erythrocytes in vitro at all concentrations assayed. These results suggest that StSBTc-3 could be evaluated as a new agent to be used in the treatment of thromboembolic disorders such as strokes, pulmonary embolism and deep vein thrombosis.